Controlling the Adsorption of β-Glucosidase onto Wrinkled SiO2 Nanoparticles To Boost the Yield of Immobilization of an Efficient Biocatalyst - Pota, Giulio (Langmuir : the ACS journal of surfaces and colloids, 2023)
β-Glucosidase (BG) catalyzes the hydrolysis of cellobiose to glucose, a substrate for fermentation to produce the carbon-neutral fuel bioethanol. Enzyme thermal stability and reusability can be improved through immobilization onto insoluble supports. Moreover, nanoscaled matrixes allow for preserving high reaction rates. In this work, BG was physically immobilized onto wrinkled SiO2 nanoparticles (WSNs). The adsorption procedure was tuned by varying the BG:WSNs weight ratio to achieve the maximum controllability and maximize the yield of immobilization, while different times of immobilization were monitored. Results show that a BG:WSNs ratio equal to 1:6 wt/wt provides for the highest colloidal stability, whereas an immobilization time of 24 h results in the highest enzyme loading (135 mg/g of support) corresponding to 80% yield of immobilization. An enzyme corona is formed in 2 h, which gradually disappears as the protein diffuses within the pores. The adsorption into the silica structure causes little change in the protein secondary structure. Furthermore, supported enzyme exhibits a remarkable gain in thermal stability, retaining complete folding up to 90 °C. Catalytic tests assessed that immobilized BG achieves 100% cellobiose conversion. The improved adsorption protocol provides simultaneously high glucose production, enhanced yield of immobilization, and good reusability, resulting in considerable reduction of enzyme waste in the immobilization stage